Implementation of Interactive Multimedia to Improve Understanding of Arabic Rules in Jar and Athaf Letters - Yusuf , Muhammad; Arif, Muh (Language Development Center, 2022)
Background: Along with the main task of teachers, namely teaching, in the teaching and learning process that takes place at school, teachers are not only required to be able to convey subject matter, but are required to be able to guide and encourage students to learn more actively. Purpose: The purpose of this study was to improve students' understanding and enthusiasm in learning Arabic on the material of jar and athaf letters by using interactive multimedia methods. Method: This study used classroom action research method. Results and Discussion: Interactive multimedia methods can improve students' activeness and learning outcomes. This can be seen from the learning activeness of students in Arabic language subjects on the subject of Jar letters and Athaf letters from the pre-cycle only obtained an average of 54.25 with a qualitative index (D) “Less” increased in cycle I by 65 with an index (C) “Enough” and increased significantly in cycle II to 84.12% with a qualitative index (A) “Excellent”. Likewise, the completeness of learning outcomes in Arabic language subject matter of Jar and Athaf letters continues to increase from the pre-cycle of only 23.07% (3 students) with an average score of 61.15, then increased in cycle I to 53.83% (7 students) with an average score of 67.69. While the completeness of student learning in cycle II can reach 84.59% (11 students) with an average score of 82.30. Conclusion and Implication: Based on the results of data analysis of classroom action research, it can be concluded that the implementation of Arabic language learning on the material of Jar and Athaf letters using interactive multimedia methods has been successful for this Classroom Action Research (PTK).